Antibiotic susceptibility and clonal distribution of Staphylococcus aureus from pediatric skin and soft tissue infections: 10-year trends in multicenter investigation in China - Su, Wei; Liu, Ying; Wang, Qing; Yuan, Lin; Gao, Wei; Yao, Kai H.; Yang, Yong H.; Ma, Lin (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Skin and Soft Tissue Infections (SSTIs) Surveillance Network of S. aureus In Pediatrics in China was established in 2009 to routinely report epidemiological changes. We aimed to monitor the present antibiotic sensitivity and molecular characteristics of S. aureus and methicillin-resistant S. aureus (MRSA) from SSTIs in children nationwide and track the changes over the past decade. Methods: Patients diagnosed with SSTIs from the dermatology departments of 22 tertiary pediatric hospitals in seven geographical regions of China were recruited continuously from May 2019 to August 2021. S. aureus was isolated, and its sensitivity to 15 antimicrobials was evaluated using the broth microdilution method. The molecular characteristics of the MRSA isolates were determined through multilocus sequence typing (MLST) and staphylococcal cassette chromosome mec (SCCmec) typing. The presence of the Panton-Valentine leukocidin gene (pvl) was determined.Results: The detection rate of S. aureus was 62.57% (1379/2204), among which MRSA accounted for 14.79% (204/1379), significantly higher than the result in previous study in 2009-2011 (2.58%, 44/1075). Compared with previous study, the sensitivity to cephalosporins and fusidic acid decreased to varying degrees, while that to chloramphenicol, ciprofloxacin, clindamycin, erythromycin, gentamicin, penicillin, and tetracycline increased significantly. The sensitivity to mupirocin, trimethoprim/sulfamethoxazole (TRISUL), and rifampicin still maintained at a high level (97.90%, 99.35% and 96.66% respectively). The leading multidrug resistance pattern of MRSA and methicillin-sensitive S. aureus (MSSA) were erythromycin-clindamycin-tetracycline (55.84%; 43/77) and erythromycin-clindamycin-chloramphenicol (27.85%, 44/158) respectively.12 high-level mupirocin-resistant strains were detected, and notable differences in geographical distribution and seasonal variation were observed.The main types of MRSA were ST121 (46.08%, 94/204), followed by ST59 (19.61%, 40/204). SCCmec V (65.69%, 134/204) and SCCmec IV (31.86%, 65/204) were dominant epidemic types. ST121-V, ST59-IV, and ST22-V were the most prevalent clones nationwide. The detection rate of pvl had increased markedly from 9.09% (4/44) in 2009-2011 to 22.55% (46/204) in 2019-2021 (P<0.05).The antibiotic sensitivity and molecular characteristics of S. aureus from pediatric SSTIs has changed significantly over the past decade. To standardize medical care, provide timely and reasonable clinical treatment, and effectively manage infection control, Chinese pediatric SSTIs guidelines are urgently needed.